2018
DOI: 10.3390/ijms19020460
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as New Biomarkers for Diagnosis and Prognosis, and as Potential Therapeutic Targets in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemias (AML) are clonal disorders of hematopoietic progenitor cells which are characterized by relevant heterogeneity in terms of phenotypic, genotypic, and clinical features. Among the genetic aberrations that control disease development there are microRNAs (miRNAs). miRNAs are small non-coding RNAs that regulate, at post-transcriptional level, translation and stability of mRNAs. It is now established that deregulated miRNA expression is a prominent feature in AML. Functional studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 191 publications
(275 reference statements)
0
63
0
2
Order By: Relevance
“…It carries a poor prognosis, especially if it is associated with HCV infection; therefore, we are searching for prognostic and therapeutic biomarkers as an attempt to improve disease outcome. miR‐155 is an oncomiR that is highly expressed in different types of leukemia and lymphoma . In our study, we found very high levels of miR‐155, about seven folds, in HCV_4‐associated ALL in pediatric patients in comparison with the HCV negative leukemic group; moreover, two folds increase in the expression was detected in HCV‐negative leukemic patients in contrast to children with HCV_4 chronic infection.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…It carries a poor prognosis, especially if it is associated with HCV infection; therefore, we are searching for prognostic and therapeutic biomarkers as an attempt to improve disease outcome. miR‐155 is an oncomiR that is highly expressed in different types of leukemia and lymphoma . In our study, we found very high levels of miR‐155, about seven folds, in HCV_4‐associated ALL in pediatric patients in comparison with the HCV negative leukemic group; moreover, two folds increase in the expression was detected in HCV‐negative leukemic patients in contrast to children with HCV_4 chronic infection.…”
Section: Discussionmentioning
confidence: 47%
“…miR-155 is an oncomiR that is highly expressed in different types of leukemia and lymphoma. 4,15 In our study, we found very high levels of miR-155, about seven folds, in HCV_4-associated ALL in pediatric patients in comparison with the HCV negative leukemic group; moreover, two folds increase in the expression was detected in HCV-negative leukemic patients in contrast to children with HCV_4 chronic infection. This big difference in the level of expression denotes the oncogenic effect of miR-155 as well as its impact on HCV_4 viral load.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…12 MicroRNAs are short noncoding single-stranded RNA molecules (19-22 nucleotides) which negatively affect the function of target messenger RNAs post-transcriptionally, modifying many essential cellular functions, including proliferation, differentiation, and death. 13 Many studies have shown that miRNAs may act as oncogenes or tumor suppressors, contributing to the development of malignant cells in both solid and hematological tumors, including AML. 14 It is believed that abnormal expression of some miRNAs may affect the process of development of leukemic cells or alter the response to treatment in cases of AML.…”
mentioning
confidence: 99%